2016
DOI: 10.1016/j.thromres.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of direct oral anticoagulants in real life patients with atrial fibrillation: Results observed in four anticoagulation clinics

Abstract: Introduction: Direct oral anticoagulant (DOAC) intra-and inter-individual variability was previously reported, but its magnitude is still considered negligible for patient management. Objective: To evaluate inter-and intra-individual variability in real-world atrial fibrillation patients on dabigatran, rivaroxaban or apixaban in four Italian anticoagulation clinics and to assess the correlation between DOAC plasma concentration and creatinine-clearance (CrCl). Materials and Methods: A total of 330 consecutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
132
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(153 citation statements)
references
References 17 publications
12
132
2
Order By: Relevance
“…The target plasma concentrations of tinzaparin were 0.05, 0.1, 0.2, 0.4, 0.6, and 0.8 anti‐Xa IU/mL plasma. These concentration ranges were selected according to the pharmacokinetics of the studied agents after administration of a therapeutic relevant dose 18, 19, 20…”
Section: Methodsmentioning
confidence: 99%
“…The target plasma concentrations of tinzaparin were 0.05, 0.1, 0.2, 0.4, 0.6, and 0.8 anti‐Xa IU/mL plasma. These concentration ranges were selected according to the pharmacokinetics of the studied agents after administration of a therapeutic relevant dose 18, 19, 20…”
Section: Methodsmentioning
confidence: 99%
“…Due to the increasing prevalence of patients who are treated with DOACs in the general population, major bleedings will become a relatively frequent event in the emergency departments with an urgent need for improving diagnostic and therapeutic tools, and specific strategies related to the site of bleeding, type of drugs, anticoagulant levels, necessity of surgical, or interventional procedures [11,25]. Since patients are admitted to emergency departments after variable hours from the last DOAC dose intake and may present with several comorbidities, anticoagulant activity may not be exclusively predictable on the basis of the drug half-life and the evaluation of renal function, also because of the high inter-intra plasma level variability [26].…”
Section: Discussionmentioning
confidence: 99%
“…It has been clearly demonstrated that variability in the circulating levels of DOACs increases the risk of clinically relevant complications. Testa et al studied 330 patients receiving DOACs therapy and reported that mean inter-individual variability expressed as overall coefficient variation values for any DOAC prescribed and taken by patients was lower at peak (CV = 46%) than at trough (CV = 63%) [23]. Mean intra-individual variability was 36.6% at trough and 34.0% at peak [23].…”
Section: A Hospital-based Precision Medicine Project To Enhance Thmentioning
confidence: 99%
“…Testa et al studied 330 patients receiving DOACs therapy and reported that mean inter-individual variability expressed as overall coefficient variation values for any DOAC prescribed and taken by patients was lower at peak (CV = 46%) than at trough (CV = 63%) [23]. Mean intra-individual variability was 36.6% at trough and 34.0% at peak [23]. Correlation with creatinine clearance was poor for all DOAC drugs and only dabigatran, an inhibitor of factor IIa, showed a significant correlation at trough [23].…”
Section: A Hospital-based Precision Medicine Project To Enhance Thmentioning
confidence: 99%
See 1 more Smart Citation